Using optical tracking system data to measure team synergic behavior: Synchronization of player-ball-goal angles in a football match - Daniel, C. (2020)
The ecological dynamics approach to interpersonal relationships provides theoretical support to the use of kinematic data, obtained with sensor-based systems, in which players of a team are linked mainly by information from the performance environment. Our goal was to capture the properties of synergic behavior in football, using spatiotemporal data from one match of the 2018 FIFA WORLD CUP RUSSIA, to explore the application of player-ball-goal angles in cluster phase analysis. Linear mixed effects models were used to test the statistical significance of different effects, such as: team, half(-time), role and pitch zones. Results showed that the cluster phase values (synchronization) for the home team, had a 3.812 × 10−2 ± 0.536 × 10−2 increase with respect to the away team (X2 (41) = 259.8, p < 0.001) and that changing the role from with ball to without ball increased synchronization by 16.715 × 10−2 ± 0.283 × 10−2 (X2 (41) = 12227.0, p < 0.001). The interaction between effects was also significant. The player-team relative phase, the player-ball-goal angles relative frequency and the team configurations, showed that variations of synchronization might indicate critical performance changes (ball possession changes, goals scored, etc.). This study captured the ongoing player-environment link and the properties of team synergic behavior, supporting the use of sensor-based data computations in the development of relevant indicators for tactical analysis in sports.